Kefir : a novel source of probiotics and biomaterials - Tay, Lai Foong (2019)
Kefir is a traditional fermented beverage and the fermentation process usually involves microorganisms like lactic acid bacteria, acetic acid bacteria and yeasts. Many of these microorganisms are reported to be probiotics and exopolysaccharides (EPS) producers that could be potentially a novel source of biomaterials for drug delivery. Thus, this project aimed to isolate and identify probiotic strains from milk and water kefir followed by screening for high EPS producers. In order to maximize types of microorganisms to be cultured, we used five different selective media to recover the microorganisms in both aerobic and anaerobic conditions. A total of 236 species, corresponsing to 14 bacterial and 5 fungal genera were isolated and identified by 16S rDNA or ITS sequencing. 22 genera were isolated from water kefir and 13 genera from milk kefir. 30% of the isolates have been used in current probiotics products while the remaining were considered new. Lactobacillus kefiri, Oenococcus oeni, Sporolactobacillus sp. and Zymomonas mobilis isolated were reported to have probiotics properties but have not been commercialized yet. Secondly, EPS production was assessed by ethanol precipitation and morphology appearance method. Liquid culture was precipitated with ethanol before freeze-dried to attain the weight of EPS produced. Lactobacillus and Lactococcus genera produced higher amount of EPS than other genera which ranged between 60 mg to 80 mg. A subset of Lactobacillus and Lactococcus isolates were plated on modified agar to compare the colonies morphology when glucose is replaced by sucrose. L. satsumensis, L. hilgardii, L. nagelii and Z. mobilis produced slimy colonies in the presence of sucrose implied that sucrose could be a better carbon source for EPS production.